The Role of Proactive Nutritional Management in Preventing Unintended Weight Loss in Patients with Head and Neck Cancer Undergoing Radiotherapy: An Evidence-Based Case Report - Therisa Adareth; Wiji Lestari (Perhimpunan Dokter Gizi Klinik Indonesia, 2026)
Abstract Background: Patients with head and neck cancer undergoing radiotherapy are at high risk of nutritional deterioration due to unavoidable oromotor side effects that reduce oral intake and lead to unintended weight loss, worsening treatment tolerance and outcomes, while proactive nutritional management may mitigate this risk as suggested by clinical trials, although findings remain variable. Objectives: This study aims to evaluate the role of proactive nutritional management in preventing unintended weight loss in patients with head and neck cancer undergoing radiotherapy. Methods: A literature search was conducted in PubMed, Scopus, and Cochrane databases. Articles were screened for duplicates, relevance, and eligibility criteria. Selected studies were critically appraised for validity, clinical importance, and applicability using the Centre for Evidence-Based Medicine (CEBM) worksheet from the University of Oxford. The level of evidence was determined to guide the grade of recommendation. Results: Two randomized controlled trials met the inclusion criteria. Both studies demonstrated good validity, clinical importance, and applicability, with a level of evidence of 1. Findings were consistent, indicating that proactive nutritional management initiated at the start of radiotherapy can prevent unintended weight loss. This effect persisted despite oromotor dysfunction during treatment. Overall, the evidence supports a strong recommendation (grade A) for implementation. Conclusion: Proactive nutritional management can effectively prevent unintended weight loss in patients with head and neck cancer undergoing radiotherapy. Keywords: Head and neck cancer, radiotherapy, proactive nutrition, weightloss